2019
DOI: 10.3389/fmicb.2019.01249
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity and Mechanism of Action of Dracocephalum moldavica L. Extracts Against Clinical Isolates of Staphylococcus aureus

et al.

Abstract: Background: Dracocephalum moldavica L. is a popular traditional medicine used by many countries, which has a wide range of pharmacological effects. The aim of this work was to investigate the antimicrobial effects of D. moldavica L. extracts against clinical isolates of Staphylococcus aureus . Our results demonstrated that the minimal inhibitory concentration (MIC) for 50 and 90% of S. aureus isolates (MIC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…None of the extracts (50-400 μg.ml -1 ) exhibited cytotoxic activity, suggesting potential safety of the plant. This is in accordance with a study by Yu et al, (2019) who did not found a significant cytotoxic effect of the EtOAc extract of D. moldavica (33.3% growth inhibition at 100 μg.ml -1 ) against human epidermal keratinocyte (HaCaT) cells. To the best of our knowledge, there is no other published data on the cytotoxicity of D. moldavica extracts.…”
Section: Cytotoxic Activitysupporting
confidence: 93%
“…None of the extracts (50-400 μg.ml -1 ) exhibited cytotoxic activity, suggesting potential safety of the plant. This is in accordance with a study by Yu et al, (2019) who did not found a significant cytotoxic effect of the EtOAc extract of D. moldavica (33.3% growth inhibition at 100 μg.ml -1 ) against human epidermal keratinocyte (HaCaT) cells. To the best of our knowledge, there is no other published data on the cytotoxicity of D. moldavica extracts.…”
Section: Cytotoxic Activitysupporting
confidence: 93%
“…Similarly, in a study on the effect of antibiotics like rifampicin, polymyxin B, kanamycin and doxycyclin on reduction of S. aureus biofilm formation, only rifampicin was found to inhibit the biofilm by about 50% [56]. The effect of ADR1 metabolites on inhibition of biofilm formation as well as on the preformed biofilms was better than some previously reported metabolite extracts [57][58][59]. Inhibition of biofilm formation strongly suggested that the metabolites prevented adherence of S. aureus and MRSA cell to the polystyrene surface.…”
Section: Antibacterial Spectrum Of Adr1 Metabolites Against Significamentioning
confidence: 77%
“… 101 In an effort to meet the urgent need for new antimicrobial drug discovery and development, in recent years a lot of attention has been paid to natural products and medicinal plants due to their low toxicity, pharmacological effects and health benefits. 102 , 103 Among natural product-derived compounds, genipin has received particular attention in ophthalmology because of its effective crosslinking activities. 59 – 69 In this study, the in vitro antimicrobial effects of genipin were evaluated against clinical isolates of S. aureus, P. aeruginosa and C. albicans using an ex vivo model of corneal infectious keratitis.…”
Section: Discussionmentioning
confidence: 99%